Tendência histórica e variabilidade do brilho solar e modelagem da radiação solar em Santa Maria, RS - Paula, Gizelli Moiano de (2012)
The objectives of this study were to test the homogeneity of monthly data of sunshine period from 1912 to 2010 hours of sunshine and the period from 1968 to 2010, recalculate the descriptive statistics of sunshine daily, monthly and seasonal Santa Maria, RS, characterize the secular trend and interdecadal and interannual variability of monthly sunshine hours and adjust and test the Ångström - Prescott and Penman equation to estimate the flux density of incident solar radiation level and in different time periods of the day for Santa Maria , RS. The data of sunshine duration and solar radiation were measured at the meteorological station of the Brazilian National Weather Center (8o DISME/INMET), located in the Experimental Department, Federal University of Santa Maria. The Run tests, and the Mann-Kendall and Pettitt tests were used for analysis of homogeneity and trends in the series respectively, and the power spectral density was used for detecting annual and decadal cicles related to El Nino Oscillation Southern and Pacific Decadal Oscillation. The time series of monthly and seasonal sunshine in Santa Maria, in the period 1912-2010 are homogeneous for all months and seasons, except for the months of December and autumn. In the time series of monthly and seasonal sunshine in Santa Maria, in the period 1912 to 2010 there is no trends to increase or decrease, ie the series are stationary. There are large interannual and interdecadal variability in the time series of sunshine in Santa Maria, RS, indicating a sign of El Nino Oscillation Southern and Pacific Decadal Oscillation climate in this element. The number of sunshine daily and average monthly number of sunshine during the periods of the day, in the range from 9 to 15 hours showed decreasing trends, especially in October and spring. There is interannual variability in the series of monthly average daily sunshine and the series of sunlight at different times of day. In La Niña years increased the mean daily sunshine and the different times of day in October, November and December. In El Niño years increased the mean daily sunshine and the different times of day during the months of January and February. The estimation of the global solar radiation by the Ångström equation modified by Prescott and Penman was not precise level and time in the different sub-periods of the day, it is suggested to be tested models of other estimates of the estimate of global radiation hourly.